Athletic advisors' experiences supporting athletes through head coach transitions - Rubin, L. M.; Huml, M. R. (International Sport Coaching Journal, 2023)
Head coaches play an important role in their influence on college athletes and their academic goals. Concerns have been raised about coaches` prioritizing athletic team success over academics. Therefore, the purpose of this study was to explore the impact of head coach transition on National Collegiate Athletic Association teams` academic culture through the perspectives of athletic advisors. Interviews were conducted with 16 athletic advisors on their perceptions of the previous and new coaches` perspective on, and involvement with, academics in addition to the transition period. Findings show the importance of the relationship between coaches and athletic advisors, that advisors were quick to discern if the new coach was going to elevate or deteriorate the program`s academic culture compared with predecessors, the need for advisors` involvement in the search process for a new coach, and the role academics had in coach searches.